СОСТОЯНИЕ ДВУХ ПОПУЛЯЦИЙ Berberis iliensis M.Pop. В НИЖНЕМ ТЕЧЕНИИ РЕКИ ИЛЕ (Experimental biology, 2015)
It is given assessment of a condition of two populations rare endemic plants Berberis iliensis M.Pop. in the lower reaches river Ile.
Keywords: population